Reforma al código de la niñez y adolescencia en cuanto a establecer el número de señalamientos para la diligencia de ADN en el juicio de impugnación de paternidad - González Labanda, Carlos Humberto (2014)
The chosen topic for this thesis enunciates: “REFORMS TO THE CODE OF THE CHILDHOOD AND ADOLESCENCE AS FOR SETTLING DOWN THE I NUMBER OF SIGNALIZATIONS FOR THE DILIGENCE OF DNA IN THE TRIAL OF OBJECTION OF PATERNITY" ; in the same one they thought about as objective to "Carry out a juridical, doctrinal and critical study of character to the civil legislation and of Ecuadorian family, regarding the objection of the paternity." In a same way the hypothesis enunciates "The lack of Law that doesn't indicate the number of signalizations for the diligence of DNA, neither the form to assure the attendance from the demanded part to the same one, it injures the right to it guides her and artificial security of the part actor, in the cases of objection of paternity." To be able to end up checking each one of these expressions, I carried out a bibliographical investigation that served as foundation for the same field investigation in that the opinion of professionals of the right was obtained of who it could settle down as conclusion that the norm lack that indicates the number of signalizations for the diligence of DNA, is an artificial aberration that forces the rights of the individuals, and injuring the right to it guides her and artificial security. It is established therefore that the investigation framed in a doctrinal deep juridical analysis, enjoys of the validity and dependability that the professional approaches of lawyers with vast experience provided me, for finally to present the conclusions,recommendations and the artificial reformation to the Code of the Childhood and Adolescence that I propose as solution alternative to this problem.